Think outside the building - Rosabeth Moss Kanter, read by the Author (New York Hachette Audio, 2020)
Over a decade ago, renowned innovation expert Rosabeth Moss Kanter co-founded and then directed Harvard's Advanced Leadership Initiative. Her breakthrough work with hundreds of successful professionals and executives, as well as aspiring young entrepreneurs, identifies the leadership paradigm of the future: the ability to "think outside the building" to overcome establishment paralysis and produce significant innovation for a better world.
Keywords: Leadership; Creative ability in business